Robotics in Implant-Based and Autologous Breast Reconstruction - King, Brody W.; McCarter, Jacob H.; Burns, Heather R.; Soleimani, Shirin; Maricevich, Marco A.; Yu, Jessie Z. (Seminars in Plastic Surgery, 2023)
Autologous and implant-based breast reconstruction continues to evolve as new technology and mastectomy techniques become available. Robotic-assisted breast reconstruction represents a growing field within plastic surgery, with the potential to improve aesthetic and functional outcomes, as well as patient satisfaction. This article provides a review of indications, techniques, and outcome data supporting the use of robotic assistance in both implant-based and autologous breast reconstruction from surgeons around the world.
Keywords: robotic surgery; robotic breast reconstruction; robotic latissimus dorsi flap; robotic DIEP